2017
DOI: 10.1007/s00449-017-1742-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of carbon sources on the viability and resuscitation of Acetobacter senegalensis during high-temperature gluconic acid fermentation

Abstract: Much research has been conducted about different types of fermentation at high temperature, but only a few of them have studied cell viability changes during high-temperature fermentation. In this study, Acetobacter senegalensis, a thermo-tolerant strain, was used for gluconic acid production at 38 °C. The influences of different carbon sources and physicochemical conditions on cell viability and the resuscitation of viable but nonculturable (VBNC) cells formed during fermentation were studied. Based on the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Colony formation took about 72–80 h. In addition, colony formation time did not changed over sequential passages. This may be as a result of pH drop due to the oxidation of glucose to gluconic acid (Shafiei et al, 2017). Since pH and other fermentation parameters could not be monitored and regulated in solid culture media, acclimation in liquid culture media was used as a complementary method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Colony formation took about 72–80 h. In addition, colony formation time did not changed over sequential passages. This may be as a result of pH drop due to the oxidation of glucose to gluconic acid (Shafiei et al, 2017). Since pH and other fermentation parameters could not be monitored and regulated in solid culture media, acclimation in liquid culture media was used as a complementary method.…”
Section: Resultsmentioning
confidence: 99%
“…Acetic acid bacteria (AAB) have been used in industrial production of vinegar, gluconic acid and L -sorbose (Singh and Kumar, 2007; De Roos and De Vuyst, 2018). They can potentially be used for the production of cellulose and other biological and pharmaceutical compounds (Adachi et al, 2003; Shafiei et al, 2017). Different strains of AAB are used in vinegar production.…”
Section: Introductionmentioning
confidence: 99%
“…Fermentation samples were subjected to centrifugation at 13 000 g for 10 min. The supernatant was filtered (0·45 µm) and the concentration of glucose and gluconic acid in the supernatant was determined by HPLC (Agilent 1110 equipped with a Supelcogel C610H column), as described previously (Shafiei et al ; Shafiei et al ).…”
Section: Methodsmentioning
confidence: 99%
“…It was used for vinegar production and vinegar starter production (Ndoye et al ; Shafiei et al ; Shafiei et al ; Shafiei et al ). In 2017, Shafiei and coworkers evaluated sodium gluconate production by A. senegalensis in the batch culture at 38°C; however, cells were not able neither to consume glucose nor to produce gluconic acid at the end of stationary phase (Shafiei et al ). In addition, it was found that the cells sampled from stationary‐phase exhibited improved growth on solid culture medium containing ethanol as the main carbon source (Shafiei et al ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation